Between opportunities and threats - an analysis of Brazilian Landless Workers' movement experiences with new media technologies - Sartoretto,Paola Madrid (2016)
Recent discussions and research about the uses of digital social media platforms by social movements and protest organizations have raised questions about threats and challenges represented by these technologies. There is also a debate on whether digital social media platforms can contribute to establish and strengthen long-standing oppositional groups and structural change. In this context, this article analyses how the Brazilian Landless Workers Movement (MST) experiences and views the use of digital social media platforms in its communicative processes. Based on interviews and observations, the article shows how MST militants present ambivalent views towards platforms such as Facebook and Twitter and towards the dynamics of digital communication. Conclusions point that the main concern is threat to the organic collective character of the movement posed by individualistic digital social media platforms. Different from contemporary protest organisations, MST sees a clear separation between the movement and its media. The goal is to appropriate of and control media technologies, which brings many difficulties when dealing with digital social media platforms.